(untitled) (Acta Scientiarum. Language and Culture, 2014)
In Links, Nuruddin Farah (2003) portrays a Somali back to his country after more than two decades of exile. The scenario he meets is aSomalia already free from the dictatorship that expulsed him, but still immersed in a bloody civil war between rival militias. Farah’s narrative is largely built around extensive scenes of conversation and confront between this returnee and the Somalis who remained and became involved in the conflict. The current paper demonstrates that the reckoning made possible by these confrontations does not actually mean a leveling of blame, since Farah seems to be very specific about the main reasons for the nation’s current state of destruction.